2021
DOI: 10.1161/jaha.120.019323
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Bariatric Surgery on the Incidence of Heart Failure and Atrial Fibrillation in Patients With Type 2 Diabetes Mellitus and Obesity and on Mortality in Patients With Preexisting Heart Failure: A Nationwide, Matched, Observational Cohort Study

Abstract: Background Obesity and diabetes mellitus are strongly associated with heart failure (HF) and atrial fibrillation (AF). The benefits of bariatric surgery on cardiovascular outcomes are known in people with or without diabetes mellitus. Surgical treatment of obesity might also reduce the incidence of HF and AF in individuals with obesity and type 2 diabetes mellitus (T2DM). Methods and Results In this register‐based nationwide cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Intriguingly, we found a very low number of deaths in the BS group in the long-term when compared to non-BS controls, in line with another large Italian cohort study [ 35 ]. The reduction of mortality could be justified by the substantial weight loss, leading to the improvement/remission of dysmetabolic abnormalities, cardiovascular, respiratory, renal outcomes, cancer reduced risk, and better motility and quality of life reported after BS [ 3 , 12 , 16 , 17 , 18 , 20 , 22 , 23 , 36 , 37 ]. This is not surprising if the effects of excess fat deposition, such as increased oxidative stress, chronic inflammation, endothelial dysfunction, ectopic lipid deposition, impairments in metabolism and heart, lung, and kidney functions, are considered together with the potential effects of BS in reversing/reducing most of these unfavorable conditions [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, we found a very low number of deaths in the BS group in the long-term when compared to non-BS controls, in line with another large Italian cohort study [ 35 ]. The reduction of mortality could be justified by the substantial weight loss, leading to the improvement/remission of dysmetabolic abnormalities, cardiovascular, respiratory, renal outcomes, cancer reduced risk, and better motility and quality of life reported after BS [ 3 , 12 , 16 , 17 , 18 , 20 , 22 , 23 , 36 , 37 ]. This is not surprising if the effects of excess fat deposition, such as increased oxidative stress, chronic inflammation, endothelial dysfunction, ectopic lipid deposition, impairments in metabolism and heart, lung, and kidney functions, are considered together with the potential effects of BS in reversing/reducing most of these unfavorable conditions [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…More uncertain are the consequences of BS on hospital admissions and healthcare resource use. Many studies reported lower hospital admissions after BS [ 11 , 12 , 13 , 14 , 15 ], suggesting beneficial effects on the chronic conditions characterizing individuals with obesity, such as type 2 diabetes mellitus, cardiovascular risk factors and diseases, chronic sub-clinic inflammation, and some types of cancer [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Other authors reported an increased request for inpatient and nonprimary outpatient care during the first 6-year period, but not thereafter in post-BS patients when compared to controls [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…HF and AF risk in people with obesity, including those with T2DM, and are associated with reduced mortality in people with pre-existing HF. 105,110 Sodium glucose cotransporter-2 inhibitor (SGLT2i) treatments (originally approved for T2DM) have demonstrated benefits beyond blood glucose reduction, including lowering of body weight, blood pressure, and incidence of HF hospitalisation in people who have pre-existing HF with or without diabetes, and some have recently been approved for treatment of HFrEF and HFpEF. [111][112][113][114][115] Atrial fibrillation AF is the most common sustained arrhythmia and a frequent cause of stroke and CV death.…”
Section: Heart Failurementioning
confidence: 99%
“…Willens et al examined the effects of weight loss after bariatric surgery on EAT amount in patients with severe obesity and showed that EAT thickness, assessed by echocardiography, decreases in patients who have substantial weight loss after bariatric surgery, thus suggesting the echocardiographic EAT thickness measurement to monitor visceral fat loss during weight reduction therapies (124). Interestingly, in obese subjects, it has been demonstrated a reduction in AF burden post bariatric surgery, compared with usual care (125)(126)(127). The beneficial effect of bariatric surgery on development of AF seems to be linked to the attenuation of various hemodynamic, metabolic and inflammatory stimuli, able to favorably influence the structure and function of the heart so as to reduce the risk of arrhythmia (128).…”
Section: Eat As a New Potential Therapeutic Targetmentioning
confidence: 99%